9-Borafluoren-9-yl and diphenylboron tetracoordinate complexes of F- and Cl-substituted 8-quinolinolato ligands: synthesis, molecular and electronic structures, fluorescence and application in OLED devices. Issue 15 (23rd March 2023) - Fialho, Carina B.; Cruz, Tiago F. C.; Rodrigues, Ana I.; Calhorda, Maria José; Vieira Ferreira, Luís F.; Pander, Piotr; Dias, Fernando B.; Morgado, Jorge; Maçanita, António L.; Gomes, Pedro T.
Abstract : Tetrahedral 9-borafluoren-9-yl and diphenylboron complexes, with fluorine- and chlorine-substituted 8-quinolinolato ligand chromophores, were synthesised, characterised and applied as emitters in OLEDs. Abstract : Six new four-coordinate tetrahedral boron complexes, containing 9-borafluoren-9-yl and diphenylboron cores attached to orthogonal fluorine- and chlorine-substituted 8-quinolinolato ligand chromophores, have been synthesised, characterised, and applied as emitters in organic light-emitting diodes (OLEDs). An extensive steady-state and time-resolved photophysical study, in solution and in the solid state, resulted in the first-time report of delayed fluorescence (DF) in solid films of 8-quinolinolato boron complexes. The DF intensity dependence on excitation dose suggests that this emission originates from triplet–triplet annihilation (TTA). Density functional theory (DFT) and time-dependent density functional theory (TDDFT) studies give insight into the ground and excited state geometries, electronic structures, absorption energies, and singlet–triplet gaps in these new organoboron luminophores. Finally, given their highly luminescent behaviour, organic light-emitting diode (OLED) devices were produced using the synthesised organoboron compounds as emissive fluorescent dopants. The best OLED displays green-blue ( λ maxEL = 489 nm) electroluminescence with an external quantum efficiency (EQE) of 3.3% and a maximum luminance of 6300 cd m −2 .